Social Sensitivity in Early Children Based on Grandparenting - Galih Retno Palupi; Yuli Kurniawati Sugiyo Pranoto (BELIA Early Childhood Education Papers, 2024)
This study aims to determine the social sensitivity that comes from the care of grandparents in early childhood, where this analysis is based on aspects of social sensitivity, namely helping, self-awareness, and cooperation. Social sensitivity is a person's action to react quickly and appropriately to objects or social situations that exist in the surrounding environment. Based on the results of direct observations, it was found that the social sensitivity of young children is still not well developed. This research uses qualitative methods with interview, observation, and documentation techniques. The subjects in this study were grandmothers and grandfathers of early childhood in Sukoharjo. The results of this research show that young children have social sensitivity which is dominant in the aspect of helping. Based on the research results, the forms of grandparent care for early childhood are companionate and involved, because companionate is a form of grandparent care that is not fully involved in the individual's life because the parent still plays a role. Meanwhile, parenting is involved where grandparents are like parents of early childhood without any parenting involvement. This is because there are differences in the transition of care that occurs due to work factors and death factors.